New evidence of mis 3 relative sea level changes from the messina strait, Calabria (Italy) - Antonioli F.; Calcagnile L.; Ferranti L.; Mastronuzzi G.; Monaco C.; Orru P.; Quarta G.; Pepe F.; Scardino G.; Scicchitano G.; Stocchi P.; Taviani M. (Water, 2021)
Investigation of sea-level positions during the highly-dynamic Marine Isotope Stage 3 (MIS 3: 29–61 kyrs BP) proves difficult because: (i) in stable and subsiding areas, coeval coastal sediments are currently submerged at depths of few to several tens of meters below the present sea level; (ii) in uplifting areas, the preservation of geomorphic features and sedimentary records is limited due to the erosion occurred during the Last Glacial Maximum (LGM) with sea level at a depth of −130 m, followed by marine transgression that determined the development of ravinement surfaces. This study discusses previous research in the Mediterranean and elsewhere, and describes new fossiliferous marine deposits overlaying the metamorphic bedrock at Cannitello (Calabria, Italy). Radiocarbon ages of marine shells (about 43 kyrs cal BP) indicate that these deposits, presently between 28 and 30 m above sea level, formed during MIS 3.1. Elevation correction of the Cannitello outcrops (considered in an intermediate-to-far-field position with respect to the ice sheet) with the local vertical tectonic rate and Glacial Isostatic Adjustment (GIA) rate allows the proposal of a revision of the eustatic depth for this highstand. Our results are consistent with recently proposed estimates based on a novel ice sheet modelling technique.